Designing an mHealth application for informal carers concerning the management of behavioural and psychological symptoms of dementia: a need analysis survey - Thilanka Jagoda; Samath D. Dharmaratne; Sarath Rathnayake (BMC, 2024)
Abstract Background Informal carers face difficulties and challenges when dealing with the behavioural and psychological symptoms of dementia (BPSD) of their family members or friends residing at home. Mobile health (mHealth) applications are promising for educating and supporting carers. However, needs analysis studies have not been conducted in Sri Lanka to develop mHealth applications for informal carers of people with dementia. Aims To explore the needs to design an mHealth application for informal carers of people with dementia concerning the management of BPSD. Method An exploratory cross-sectional survey was conducted among a convenience sample (N = 203) of informal carers as a part of developing an mHealth application. Family members, relatives, or friends who lived with people with dementia and provided care on an unpaid basis for more than three months were included. The questionnaire included sociodemographic data, carer-rated prevalence and severity of BPSD, and informal carers' knowledge of dementia, carer burden, information-seeking sources, availability of smartphones, mHealth information seeking and perception of mHealth information seeking related to managing BPSD. Descriptive analysis and inferential tests were performed. Results Informal carers of people with dementia were predominantly female (70.4%), and 64% showed low knowledge of dementia. Of the participants, 35% reported a high carer burden, 53.7% reported a low burden, and only 11.3% reported no carer burden. Most of their care recipients (97%) had at least one BPSD. The prevalence and severity of BPSD were significantly and positively correlated with the carer burden. The participants' main source of information was health professionals. Most of them owned smartphones (63.5%), but none used mHealth applications for dementia-related information seeking. Approximately half of the respondents were ready to spend time (52.7%) and money (46.8%) on mHealth information seeking. Perceived mHealth usefulness was significantly associated with dementia knowledge, smartphone ownership, and readiness to spend time and money on mHealth information seeking. Conclusion Informal carers of people with dementia were affected by BPSD in their care recipients. This study explored carers' educational needs concerning dementia, BPSD, and carer burden. Informal carers could adapt mHealth for dementia-related information seeking. Their unmet needs in managing BPSD should be explored.